MAGMA DEGASSING AND CRYSTALLIZATION PROCESSES DURING ERUPTIONS OF HIGH-RISK NEAPOLITAN-VOLCANOES: EVIDENCE OF COMMON EQUILIBRIUM RISING PROCESSES IN ALKALINE MAGMAS - Mastrolorenzo G.; Pappalardo L. (My University, 2006)
Compositional, textural and experimental data on products from explosive and effusive eruptions of Neapolitan volcanoes (Campi Flegrei and Somma-Vesuvio) allow us to constrain degassing and fragmentation conditions during eruptions of alkaline magmas. Significant differences in compositional and textural features have been recognized between lavas, scoria and pumice resulting respectively from effusive, moderately and extremely explosive eruptions. Pumice samples have highly-vesicular glassy matrix, low microlite number density and moderate to high water content. Crystal Size Distributions (CSD) are steep with high intercept values; the narrow microlite size range indicates single nucleation event. Scoria products are characterized by moderate vesicularity and water content. They have high number density of microlites which are bimodal in size. CSD show distinct inflections that are explained as two crystal populations growing in distinct time. Lava samples generally have low vesicularities, moderate to high microcrystalline groundmass and low glass water content. The comparison between textural and compositional features of natural rocks with samples obtained by decompression experiments allows us to conclude that degassing processes during magma ascent occurs in near-equilibrium conditions even at high decompression rate. Moderate to long magma rise times, calculated in the order of a few days, produce open-degassing responsible for moderately explosive to effusive activity. Short magma rise times, calculated in the order of a few hours, result in closed-system degassing that allow explosive fragmentation when the volume of growing bubble reaches a fixed threshold. Vesicularity and water content measured on matrix glass of pumice indicate that this process occurs at pressure of 10-30 MPa. In these conditions, degassing, fragmentation and in turn the eruptive style is strongly influenced by initial conditions in the magma chamber (volatile content, temperature, pressure) instead of decompression rate, in contrast with that observed for rhyolitic melts. These differences have important consequences in terms of volcanic hazards and risk. The low-viscosity alkaline magma is able to maintain efficient degassing even during the final stage of magma ascent, favoring, in the case of closed-system, fragmentation and explosive activity. © 2006 Elsevier B.V. All rights reserved.
Keywords: CAMPI FLEGREI AND SOMMA-VESUVIO; CRYSTALLIZATION; DEGASSING; EXPLOSIVE ERUPTIONS; VESICULATION